The Genesis of the Institute of Criminal Punishment in Forced Works - V. B. Spitsnadel (Теоретическая и прикладная юриспруденция)
The article is devoted to the peculiarities of the formation of the legal basis for the execution of this type of criminal punishment, like forced labor. The scientific paper uses formal-logical, historical and comparative-legal research methods. The history of the appearance and development of this type of punishment is analyzed, the study of the straitjackets. workhouses and penitentiary detachments as a prototype of modern correctional centers is being conducted. The results of the first year of compulsory labor in the Russian Federation were summed up. The main problems and difficulties associated with the execution of punishment in the form of forced labor are indicated.